Case report: A novel COL3A1 variant in a Colombian patient with isolated cerebrovascular involvement in vascular Ehlers–Danlos syndrome - Valencia-Cifuentes, Valeria; Sinisterra-Díaz, Stiven Ernesto; Quintana-Peña, Valentina; Folleco, Edgar; Nastasi-Catanese, José A.; Pachajoa, Harry; Fernández-Cubillos, Juan P. (Frontiers in Medicine, 2024)
To date, approximately 600 unique pathogenic variants have been reported in COL3A1 associated with vascular Ehlers-Danlos syndrome (vEDS). The objective of this study was to describe a patient with a novel variant in COL3A1 associated with vEDS.We describe the clinical history and thorough phenotyping of a patient with brain aneurysms and an identified novel pathogenic variant in COL3A1.This male patient reported transient focal neurologic symptoms. Physical examination showed abnormal atrophic scarring, horizontal stretch marks under the arms, and acrogeric appearance of the skin of the hands and feet. Brain imaging revealed extensive dilation of both internal carotids and the vertebrobasilar system. Molecular analysis identified a variant in COL3A1 (NM_000090.4):c.3058G>T p.(Gly1020Cys), that we classified as likely pathogenic. Currently, the patient has never had an event concerning dissection/rupture of tissues that could be affected in this condition.This report demonstrates that exhaustive evaluation with clinical and genetic approaches should be considered in patients with vascular abnormalities. vEDS has a variable clinical presentation and often goes unrecognized, even though it is related to life-threatening complications and a shortened life expectancy. Diagnosis confirmed by genetic testing is crucial to determining appropriate surveillance, prevention, treatment, and genetic counseling.